Policing the poor through space: The fil rouge from criminal cartography to geospatial predictive policing - Gatti Carlo (Oñati International Institute for the Sociology of Law, 2022)
Recent years have witnessed an explosion of interest in predictive policing, with a clear opposition emerging between supporters and critics of its implementation. While critical accounts conventionally centre on opacities and operational asymmetries of the algorithmic construct (biased training, feedback loop, etc.), I argue that a different critique is first needed. Focussing on place-based techniques, I maintain that contemporary predictive mapping basically perpetuates the political and epistemic dictates which have historically framed the conceptualisation of crime in relation to space. Through a review of sources spanning from the Cartographic School to current predictive policing literature, I identify two main conceptual axes which operationalise this heritage: first, an explanatory framework of crime that has never detached from the socio-economic deficit archetype; and secondly, an ontologisation of crime alternative to biologicist positivism, nonetheless integral to the etiologic paradigm. Therefore, without first disputing these ideological bottlenecks, no initiative towards a transparent use of predictive policing is plausible, neither does a sharp distinction between place-based and person-based predictions seem tenable.